Oportunidades y amenazas para la Argentina en el comercio Sur-Sur - CEI - Centro de Economía Internacional (Buenos Aires) (Centro de Economía Internacional (CEI), 2004)
– The South-South trade offers a wide spectrum of opportunities for developing countries, given the complementary feature existing and the underexploitation of trade among the economies in the hemisphere. For the purpose of taking advantage of those opportunities, in June 2004, the third round of negotiations of the Global System of Trade Preferences (Sistema Global de Preferencias Comerciales - GSTP) among Developing Countries, a mechanism created by the G-77 in 1982 to promote the South-South trade, was launched in Sao Paulo (UNCTAD XI United Nations Conference on Trade and Development). In this paper, the impact that a broadening of the GSTP agreement may have on the Argentine trade is estimated by using different approaches: i) quantification of the trade that is currently performed under the generalized system of trade preferences (GSTP) among developing countries (PEDs); ii) general equilibrium estimation of the impact of a liberalization of trade among developing countries; iii) analysis of the trade complementarity among the GSTP countries; and iv) partial equilibrium estimation of the impact of a liberalization of trade among developing countries in such key sectors as agriculture, textile, among others.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Süd-Süd-Beziehungen; Argentinien